A rapid hydrophilic interaction liquid chromatographic determination of glimepiride in pharmaceutical formulations - Si Zhou; Pengxiao Zuo; Yuegang Zuo; Yiwei Deng (Elsevier, 2017)
Glimepiride is one of the most widely prescribed antidiabetic drugs and contains both hydrophobic and hydrophilic functional groups in its molecules, and thus could be analyzed by either reversed-phase high performance liquid chromatography (HPLC) or hydrophilic interaction liquid chromatography (HILIC). In the literature, however, only reversed-phase HPLC has been reported. In this study, a simple, rapid and accurate hydrophilic interaction liquid chromatographic method was developed for the determination of glimepiride in pharmaceutical formulations. The analytical method comprised a fast ultrasound-assisted extraction with acetonitrile as a solvent followed by HILIC separation and quantification using a Waters Spherisorb S5NH2 hydrophilic column with a mobile phase consisting of acetonitrile and aqueous acetate buffer (5.0 mM). The retention time of glimepiride increased slightly with decrease of mobile phase pH value from 6.8 to 5.8 and of acetonitrile content from 60% to 40%, indicating that both hydrophilic, ionic, and hydrophobic interactions were involved in the HILIC retention and elution mechanisms. Quantitation was carried out with a mobile phase of 40% acetonitrile and 60% aqueous acetate buffer (5.0 mM) at pH 6.3, by relating the peak area of glimepiride to that of the internal standard, with a detection limit of 15.0 μg/L. UV light absorption responses at 228 nm were linear over a wide concentration range from 50.0 μg/L to 6.00 mg/L. The recoveries of the standard added to pharmaceutical tablet samples were 99.4-103.0% for glimepiride, and the relative standard deviation for the analyte was less than 1.0%. This method has been successfully applied to determine the glimepiride contents in pharmaceutical formulations.